Evaluación del efecto del agua magnetizada en el desarrollo de plantas de quinua (chenopodium quinoa) variedad iniap “pata de venado” en la etapa fenológica de crecimiento en Salache – Cotopaxi. - García Sanmartin, Nelson Bryan (2020)
This project was carried out at the Salache Experimental campus at the Universidad Técnica de Cotopaxi linked to the Andean Grains and Smart Greenhouse project. Of the research objetives are: To evaluate the effect of magnetized water on the development of quinoa plants Pata de Venado variety in the phenological stage of growth To determine the net demand of the magnetized water for the quinoa cultivation variety Pata de Venado to Characterize the agronomic behavior of the Pata de Venado quinoa plants in the phenological stage of growth with the application of magnetized water; To analyze the behavior of chemical parameters of the substrate with the use of magnetized water. A randomized complete block design with four treatments and five repetitions was used. Treatments 1, 2 and 3 are magnetized water with intensity of 1000, 3000 and 5000 Gauss. While treatment 0 is water without subjecting to magnetic fields. It was determined the net demand for irrigation 53.61 l / m2 * month applying the Oudinn methodology. The results of the behavior of the chemical properties of water with the use of magnetic fields were shown to influence the pH of 5.5-6.5 to 8.50 and electrical conductivity when rising in T3. In terms of hardness, it fell from 308.8 of T0 to 120.3 CaCo3 dS / m of T1, while RAS, Calcium, Magnesium, Sodium, Potassium and Sulfide parameters lower their values. Boron increases its value....